Analisis Yuridis Qanun Jinayat dalam Strukturisasi Hukum Pidana Nasional - Erfin Dermawan Surbakti; Endang Agoestian (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
The Nanggroe Aceh Darussalam is a city that is thick with Islamic law. It has a population of around 5,281,891 people, the majority of whom are Muslim. Particular regions that have special autonomy. Evidenced by the existence of Law No.4 of 1999 regarding the implementation of Special Autonomy for Aceh province. As regulated in 1999 to 2004, it has allowed local governments to issue (PERDA) regional regulations. The PERDA launched by the Aceh government is the Qanun Jinayah, but by issuing regional regulations, it must not conflict with existing laws or higher laws. The existence of this study aims to analyze the Qanun Jinayah in the structuring of criminal law. To know the presence, implementation, and reflection of the Qanun Jinayah. The method used is using a qualitative descriptive analysis approach with data collection techniques by triangulation. The results of this study confirm that the existence of Qanun Jinayah is recognized as a national parent. There is no conflict between the contents of the Qanun Jinayah and the National Criminal Law. The implementation carried out can provide output that Aceh has a new law. However, the existence of Qanun Jinayah cannot be separated from the reflection of society, which leads to a sociological, philosophical, and juridical foundation.